2018
DOI: 10.1039/c8ra00425k
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the molecular mechanism underlying CD4-dependency and neutralization sensitivity of HIV-1: a comparative molecular dynamics study on gp120s from isolates with different phenotypes

Abstract: The envelope (Env) of HIV-1 plays critical roles in viral infection and immune evasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 74 publications
(140 reference statements)
0
12
0
Order By: Relevance
“…Our previous simulation studies on gp120 from two extreme neutralization phenotype HIV strains also revealed the effect of mutations on structural dynamics. 29 Our team is preparing a study on more in-depth molecular dynamics of gp120 from different HIV-1 isolates. Like the case study about NPAC, 30 a cytokine-like nuclear factor involved in chromatin modication and regulation of gene expression, we expect to identify key mutations that affect the conformational exibility of gp120 in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous simulation studies on gp120 from two extreme neutralization phenotype HIV strains also revealed the effect of mutations on structural dynamics. 29 Our team is preparing a study on more in-depth molecular dynamics of gp120 from different HIV-1 isolates. Like the case study about NPAC, 30 a cytokine-like nuclear factor involved in chromatin modication and regulation of gene expression, we expect to identify key mutations that affect the conformational exibility of gp120 in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Note that for the unliganded and CD4-complexed gp120s, the first two eigenvectors cumulatively contribute 40.5% and 51.8% to TMSF, respectively. Our previous work 28,32,33 and other studies 26,34 have shown that the first few eigenvector projections are good reaction coordinates capable of distinguishing among different conformational states/substates sampled by MD simulations; furthermore, the evaluation of conformational sampling with cosine contents of the first few eigenvectors indicates that our ms-scale multiplereplica MD simulations have achieved a sufficient convergence of the conformational sampling. Therefore, our constructed FELs are accurate enough to provide reliable information on the thermodynamics and kinetics of the two forms of gp120 near their starting states.…”
Section: Collective Motionsmentioning
confidence: 54%
“…6A). 25,32 In such a stable ground state, the vulnerable epitopes recognized by the highly potent neutralizing antibodies are buried, whereas the immunodominant epitopes recognized by the non-neutralizing or less potent antibodies are exposed. 16,44,45 Therefore, before viral infection, the stable maintenance of gp120 close to the unliganded state provides a thermodynamic basis for HIV-1 neutralization resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each system was subjected to 1000 steps of steepest-descent energy minimization followed by 1000 steps of conjugate-gradient minimization. The last minimization was followed by four successive 100 ps position-restrained MD simulations in the isochoric-isothermal (NVT) ensemble, with protein heavy atoms and Ca 2+ restrained by the harmonic potential with reduced force constants (i.e., Kposres ¼ 1000, 100, 10, and 0 kJ mol À1 nm À2 ) 38,40 and temperature maintained at 300 K using a velocity rescaling thermostat. 41 Finally, at each of the three temperatures (i.e., 283, 300, and 343 K, which are the approximate habitat temperatures of the source organisms of VPR, PRK, and AQN, respectively), ve 30 ns production MD runs were performed in the NPT ensemble.…”
Section: Simulationsmentioning
confidence: 99%